Riscos ergonômicos: uma análise do posto de trabalho da secretaria geral de graduação da UFPA - Campus Abaetetuba por meio do checklist - ORMESINO, Priscila de Carvalho (2019)
In developing the present work, the general objective was to analyze the ergonomic risks of the post of the General Secretariat of Graduation of the UFPA-campus of Abaetetuba through a qualitative characteristic methodology that through bibliographical researches, consultations and academic works related to the theme and especially the work of Couto (2014) on the methodology check-list favored the full development of the work. From this, questionnaires were applied to the employees of the UFPA's General Secretariat of Graduation, and the questionnaires were completed in a group, where the readings of the questions were done so that the group could respond in a way that was in line with the reality of the workplace. It is worth mentioning that in the present study the check-list methodology was not used to define whether a person is at risk of injury or not, much less to perform an implication of some disorder presented by the employee in the development of his work, since for this it is necessary to use other tools and a detailed analysis of the occupational exposure of the worker. After the application of the questionnaire, followed by an analysis of the results, it can be verified that the UFPA undergraduate work station is consistent with the proposal of a good ergonomic condition which contributes to a good development and accomplishment of the work.